Implementasi Pendidikan Kemandirian Di Pesantren Mahasiswa Garawiksa Yogyakarta - Santoso, Fattah Setiawan; Nasruddin, Muhammad; Siswadi, Siswadi; Imroatun, Imroatun; Maftukhatusolikhah, Maftukhatusolikhah (Universitas Cokroaminoto Yogyakarta, 2022)
The purpose of this study was focused on deepening independent character learning through Islamic Religious Education (PAI) at the Garawiksa Student Islamic Boarding School Yogyakarta (PMGY). Such research has had a great impact on the consistency of PAI in pesantren while still following the initial goal of the pesantren institution in educating its students to be able to live independently which is beneficial for the surrounding community. Through qualitative research with a case study pattern, it can be concluded that independence education at PMGY is directed at its basic values ​​with the dimensions of developing the spirituality, intellectuality and professionalism of the students. Such PAI was then supported by inculcating the values ​​of togetherness and simplicity through pesantren policies. The figure of a democratic caregiver/kyai with an interaction pattern that prioritizes a cultural approach has offered pesantren programs that can explore the full potential and uniqueness of each student so that they are accustomed to solving problems independently.